THE EFFECTIVE USE OF REFLECTIVE TEACHING STRATEGY IN SCHOOL EDUCATION - Dr. Archana Ramesh Visave (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The approach of reflective teaching in education usually changes the way we teach, and we have a role to play in the teaching process. Teachers who seek their own education through critical reflection change their attitude and awareness, which they believe can benefit their professional growth as a teacher as well as improve student support. Like other forms of self-inquiry, reflective teaching does not pose a risk, as writing a journal; self-reporting or recording lessons can be time consuming. However, teachers are so involved in reflective analysis of their own pedagogy that it is a valuable tool for self-assessment and professional growth. Reflective learning suggests that experience alone is insufficient for professional growth, but this experience with reflection can be a powerful stimulus for teacher development.